Research on the Language and Related Problems of Chen Fu Agricultural Book - Ling Xu , Jingjing Peng , Zhuojing Wu , Zunzhang Sun , Cheng Xia (Forest Chemicals Review)
The Proofread of Chen Fu Agricultural Book plays an important role in explaining and studying Chen Fu Agricultural Book, but there are still some improvements in Sentence pause and word use. By comparing several modern annotation versions of Chen Fu Agricultural Book, listing the differences between annotation versions with the help of relevant ancient books, analyzing and correcting their Sentence pause and word errors, we can clarify the disputes and puzzles in the use of words and sentence breaks in Chen Fu Agricultural Book.